2012
DOI: 10.1136/neurintsurg-2012-010438
|View full text |Cite
|
Sign up to set email alerts
|

Difficult catheter access to the occluded vessel during endovascular treatment of acute ischemic stroke is associated with worse clinical outcome

Abstract: Difficult catheter access to target the carotid is common during acute endovascular treatment of stroke patients and is associated with a worse clinical outcome. If transfemoral access appears difficult, alternative access such as direct carotid puncture could be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 22 publications
3
148
3
1
Order By: Relevance
“…11) While the lesions could be accessed in a median time of 20 minutes from femoral artery puncture in easily accessible cases, about 30 minutes was reportedly wasted in poorly accessible cases. 11) Difficult catheter access is considered an adverse prognostic factor, 11) and shortening of the access time is vital. At our hospital, change of the approach route is considered if more than 30 minutes is needed from puncture to the placement of the guiding catheter.…”
Section: Resultsmentioning
confidence: 99%
“…11) While the lesions could be accessed in a median time of 20 minutes from femoral artery puncture in easily accessible cases, about 30 minutes was reportedly wasted in poorly accessible cases. 11) Difficult catheter access is considered an adverse prognostic factor, 11) and shortening of the access time is vital. At our hospital, change of the approach route is considered if more than 30 minutes is needed from puncture to the placement of the guiding catheter.…”
Section: Resultsmentioning
confidence: 99%
“…approach was chosen only for patients who switched from unsuccessful TFA. [4][5][6] Haussen et al 4) reported 15 patients who underwent endovascular treatment for acute ischemic stroke via the TRA. In 12 of these, the TFA was unsuccessful, requiring a switch to the TRA.…”
Section: Resultsmentioning
confidence: 99%
“…However, other factors, such as aortic tortuosity, prolong the access time in some patients. Ribo et al 6) reported that the recanalization rate was low in patients with an access time of ≥30 minutes, and that many patients showed an unfavorable outcome. According to several studies, the route was changed, or the use of devices was devised in such patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations